The kinetic relativity theory – hiding in plain sight - Loen Mark V. (Open Physics)
A question in physics is whether Special Relativity (SR) is the only theory that explains relativistic behavior. SR measures time dilation by a relative velocity between two frames. Laboratory experiments with a single moving body fit this concept. However, GPS satellites and their ground clocks measure time dilation by a velocity relative to a common non-rotating Earth inertial frame. To better understand the conceptual difference, an experimental survey was undertaken. The survey analysis showed that laboratory experiments also fit into the non-rotating Earth frame concept. The laboratory experiments only need to add the Earth rotational velocity to both the laboratory frame and the moving frame. The analysis also revealed that the relative velocity calculation was astonishingly close to the common Earth frame calculation. The common Earth frame then becomes the explanation for all experimental types. And it signifies that a gravity field – moving body interaction causes relativistic effects. The experimental record also contained enough data to draft an empirical kinetic theory different than SR. The “no preferred reference frame” of SR is replaced by “there is a preferred reference frame.” And the preferred frame is the nearby Earth gravity field.